Photoswitchable fluorescent dyes for RESOLFT super-resolution microscopy - Leslie, K (2023)
Super-resolution fluorescence microscopy, which allows the resolution of features below the diffraction limit of light, has transformed our ability to investigate cellular processes on the nanoscale. This thesis describes the synthesis, characterisation and testing of photoswitchable fluorescent dyes for application in RESOLFT super-resolution microscopy.